PENGGUNAAN PEMBELAJARAN LEARNING CYCLE DI BANTU MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SD PADA MATERI SIKLUS AIR - Yeni Hendra; Mery Berlian; Al-Amin (JIP: Jurnal Ilmu Pendidikan, 2025)
Based on initial observations, data was obtained showing that students' science learning outcomes were still low. This was due to the conventional learning system and the lack of tools to help students understand the learning material. Therefore, research was conducted with the aim of improving science learning outcomes through the use of the learning cycle model with image media. This research was classroom action research, which was carried out in two cycles. The stages included planning, implementation, observation, and reflection. The data collection methods used included written tests, observation sheets, and documentation. Data analysis used descriptive statistics. The subjects in this study were 14 third-grade students at SD Negeri 14 Langung Sepakat, Rao Utara. From the results of the pre-cycle data analysis, the classical mastery level was 42.86% with an average score of 60.00, which was considered sufficient. After the PTK was conducted, there was an increase in the average science learning outcomes of students in each cycle. In cycle I, the classical mastery percentage was 64.29% with an average score of 67.86, then in cycle II, the classical mastery percentage was 92.86% with an average score of 86.42, with a Very Good criterion. From these results, it can be concluded that the use of the learning cycle model with image media can improve students' science learning outcomes, so that it can be used by teachers as one of the learning models in science lessons.